Chronic Disease in Health Emergencies: In the Eye of the Hurricane - Earl S. Ford, MD, MPH; Ali H. Mokdad, PhD; Michael W. Link, PhD; William S. Garvin; Lisa C. McGuire, PhD; Ruth B. Jiles, PhD; Lina S. Balluz, ScD, MPH (Centers for Disease Control and Prevention, 2006)
Introduction Inadequately controlled chronic diseases may present a threat to life and well-being during the emergency response to natural disasters. An estimate of the possible numbers of people who may require treatment for chronic diseases should help in planning a response, but such information for local areas is not easily accessible. We explored how a current surveillance system could be used to provide estimates of the potential needs for emergency treatment of chronic diseases in the wake of a natural disaster. Methods We used data from adults aged 18 years or older who participated in the Behavioral Risk Factor Surveillance System (BRFSS) in 2004 to estimate the prevalence and numbers of people with diabetes, heart disease, stroke, hypertension, and current asthma who lived in the New Orleans-Metairie-Kenner, La, metropolitan statistical area. Results About 9.0% of participants had diabetes, 4.6% had angina or coronary heart disease, 3.0% had had a myocardial infarction, 2.0% had had a stroke, and 6.3% had current asthma. About 25.4% adults had at least one of the above conditions. Conclusion A surveillance system such as the BRFSS can provide potentially useful baseline information about the numbers of people with chronic diseases and the treatment that they receive; this information can assist the medical and public health community in assessing the needs of people with chronic diseases after disasters and in planning relief efforts.